The Effect of Mergers and Acquisitions on Firms Operating in the Western European Insurance Sector - Bucci, Edoardo (2015)
In this work we wish to assess whether mergers and acquisitions in the insurance sector have been beneficial to both acquiring and target companies, in terms of profitability and value created for shareholders, and to what extent. We focus on transactions between acquirers belonging to the financial sector and target insurance firms, both based in Western Europe, along a time horizon spanning from 1994, when the EU Third Generation Insurance Directive was introduced, to 2011, a timespan that allows us to cover both upturns and downturns in the market. The minimum deal size is set at € 5 Million. Our approach is comprehensive, including both a fairly standard event study on the stock price performance of acquiring companies and an operating performance study, aimed at assessing whether the profitability of both acquirers and targets improves after an M&A deal with respect to either their pre-merger profitability, or the performance of a control group of financial companies. The event study is carried out basing on two key indicators, namely, the standardised average abnormal returns (SAARs) and the standardised cumulative abnormal returns (SCARs), while the operating performance study focuses on three profitability ratios: ROE, ROA and Profit Margin (plus the Combined Ratio for target insurance firms), on which paired t-tests, Wilcoxon Rank-Sum tests and unpaired t-test with Welch’s correction are conducted. We show how acquiring insurance firms (again based in Western Europe) is significantly detrimental to the acquirers’ stock price performance and to their operating performance. These conclusions regarding acquiring firms are fairly in line with the literature on event studies; the literature on operating performance studies, however, does not present a dominant trend to refer to. The case of target firms is more ambiguous and hard to interpret; in general, however, a slight improvement in profitability can be noticed. Again, we have to compare these conclusions with a literature that is not unequivocal in its orientation, although in the case of targets a generally positive or at least non-negative trend can be recognised; the few significant differences and the wide non-rejection of the null hypothesis of difference in performance in our study point in that direction.